The Impact of Emotional Design on Multimedia Learning Outcomes: The Moderating Role of Task Difficulty - Zhihong Liu; Zhenhong Wang (Behavioral Sciences)
Previous studies have demonstrated that emotional design can enhance multimedia learning outcomes. However, it is unknown whether task difficulty moderates the effect of emotional design on multimedia learning outcomes. This study aimed to explore this issue with the emotional design of multimedia learning materials in middle school mathematics probability knowledge learning. A 2 (emotional design vs. neutral design) × 3 (low, medium, and high task difficulty) between-subjects design was used to examine how emotional design affects multimedia learning outcomes in 180 middle school students under different levels of task difficulty. The results showed that the emotional design significantly elicited positive emotions among learners. Emotional design significantly only enhanced multimedia learning outcomes under medium-task-difficulty conditions (p < 0.001, ηp2 = 0.09), but not under low- and high-task-difficulty conditions. These findings suggest that task difficulty is a crucial moderator of the effect of emotional design on multimedia learning outcomes.